2010
DOI: 10.1002/adma.201003304
|View full text |Cite
|
Sign up to set email alerts
|

Chemical Sensing with Polyaniline Coated Single‐Walled Carbon Nanotubes

Abstract: A positive synergy: Single‐walled carbon nanotube/polyaniline (SWNT/PAni) nanocomposite with controlled core/shell morphology was synthesized by a noncovalent functionalization approach. Unique electron interactions between the SWNT core and the PAni shell were studied electrochemically and spectroscopically, and superior sensor performance to chemical gases and vapors was demonstrated.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
78
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 102 publications
(79 citation statements)
references
References 34 publications
1
78
0
Order By: Relevance
“…Fig. 4(d) reveals the detailed spectrum of the C element, with the peak of C 1s electrons at binding energies of 284.22 eV and 285.0 eV corresponding to the sp 2 -hybridized graphite-like carbon atoms of MWCNTs and the sp 3 -hybridized carbon atoms in a disordered structure, respectively.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Fig. 4(d) reveals the detailed spectrum of the C element, with the peak of C 1s electrons at binding energies of 284.22 eV and 285.0 eV corresponding to the sp 2 -hybridized graphite-like carbon atoms of MWCNTs and the sp 3 -hybridized carbon atoms in a disordered structure, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…[1][2][3] It was found that the transport behavior of the carbonaceous species depends on the morphology and structural perfection of the CNT; e.g. single-walled carbon nanotubes (SWCNTs) or their bundles show classical transport properties such as Coulomb blockade, level quantization, Luttinger liquid characteristics, and ballistic transport, for example.…”
Section: Introductionmentioning
confidence: 99%
“…They have been already in extensive use in order to immobilize desired chemical species for development of technological applications [22][23][24][25][26][27][28][29]. PANI is unique in the family of the conducting polymers due to its reversible doping/de-doping properties based on acid/base reactions [30,31]. The doped polyaniline has many features, such as better solubility, redox activity as well as conductivity over a wider pH range [32][33][34].…”
Section: Introductionmentioning
confidence: 99%
“…Understanding heterogeneous electron transfer (HET) at CNTs is of considerable importance, due to the wide range of electroanalytical and electrocatalytic systems based on CNTs (14)(15)(16)(17), and also because electrochemistry provides an attractive route to functionalize and tailor the properties of CNTs (18)(19)(20). Probing HET in 1D electrode materials is interesting fundamentally, given their inherent electronic structure and properties (21,22).…”
mentioning
confidence: 99%